Contribution of intraoperative parathyroid hormone monitoring to the surgical success in minimal invasive parathyroidectomy - Akgün, Ismail Ethem; Ünlü, Mehmet Taner; Aygun, Nurcihan; Kostek, Mehmet; Uludag, Mehmet (Frontiers in Surgery, 2022)
Background: The contribution of intraoperative parathyroid hormone monitoring to minimally invasive parathyroidectomy remains controversial. We aimed to evaluate whether intraoperative parathyroid hormone monitoring monitoring could contribute to minimally invasive parathyroidectomy in these patients. Methods: The data of the patients whose preoperative ultrasonography and technetium-99m sestamibi scintigraphy imagings were positive and concordant for one gland and who underwent minimally invasive parathyroidectomy between 2003-2018 in our clinic, were evaluated retrospectively. Blood samples were collected at pre-excisional period, and at post-excisional 10th and 20th minutes; the intaoperative parathyroid hormone was measured, and the surgery was terminated without waiting for the result. Patients were divided into 2 groups according to the postoperative results, as those with normocalcemia (Group 1) and those with persistence (Group 2). Results: There were 195 patients in Group 1 and 14 patients in Group 2. The cure rate at the first surgery was 93.3%. Cure was achieved after the second operation in all patients in Group 2. Recurrent disease developed in 1 patient in group 1 and the overall cure rate was 99.5%. If intraoperative parathyroid hormone had been evaluated, cure could have been achieved at the first surgery with additional exploration, in 10 (71.4%) of 14 patients according to the insufficient decrease in parathyroid hormone value at the 10th minute in Group 2, and in 9 (64.3%) of 14 patients according to the parathyroid hormone value at 20th minute. However, due to insufficient decrease (false negative) in the parathyroid hormone value at the 10th minute and 20th minute the rate of false negatives and unnecessary exploration would be 9.5% and 2.5%, respectively. With additional exploration, the cure rate in the first surgery could be increased by 4.3% to 97.6% according to the 20th minute intraoperative parathyroid hormone value. Conclusion: The cure rate in minimally invasive parathyroidectomy can be increased by minimizing unnecessary conversion to bilateral neck exploration, by evaluating intraoperative parathyroid hormone at 10th minute in patients with positive and concordant scans, and intraoperative parathyroid hormone at 20th minute in patients with inadequate decrease at 10th minute intraoperative parathyroid hormone.